Faktor-Faktor yang Mempengaruhi Opini Auditor Independen di Kota Palembang - Siddik, Sa'adah; Yudha, Astro (Universitas Muhammadiyah Palembang, 2016)
The problems of this study were how the partial influence of the auditor’s opinion skills, independence, due profesional care, audit evidence on the auditor opinion was, and how the simultaneous influenceof the auditor‘: skills, independence, due professional care, audit evidence on the auditor‘ opinion was. The objektives of this study were to find ont the partial influence of the auditor‘: skills, independence, due professional care, audit evidence on the auditor’ opinion, and to find ont the simultaneons in?uence of of the auditor’: skills, independence, due professional care, audit evidence on the auditor’ opinion. The independent variables in this study werw auditors’ skills, auditor‘: independence, auditor‘: due professional care, auditors’ audit evidence, the while dependent variable was auditors’ opinion . This study used and associative method. The data of this study used primary and secondary data, the techniques for collecting data were using interviews and documentation. The method for analizing the data used quantitative analylisis method. The result showed that the auditors’ skill of die auditors’ skill independence, due professional care, audit evidence simultaneonsly in?uenced the auditors‘ opinion. Partially the auditors’ skill, auditors’ independence, and audit evidence in?uenced the auditors‘ opinion, while the auditors’ due professional care did not signi?cantly in?uenced the auditors opinion